Computed tomography analysis of multicorer SO268/2_107-1, core 11 - Jürgen Titschack; Sophia Stavrakoudis; Massimiliano Molari; Batuhan Çağrı Yapan; Julia Marén Otte; Felix Janssen; Christian Timann; Arne-Jörn Lemke (PANGAEA, 2024)
Selected multicorer cores of R/V Sonne cruise SO268-2 were scanned by a Toshiba Aquilion 64 computer tomograph (CT) at the hospital Klinikum Bremen-Mitte with an x-ray source voltage of 120 kV and a current of 600 mA. The CT image stacks have a resolution of 0.35 mm in x/y-direction and 0.5 mm resolution in z-direction (0.3 mm reconstruction unit). Images were reconstructed using Toshiba extquotesingles patented helical cone beam reconstruction technique (TCOT) and are provided in DICOM-format. The data were processed with the ZIB edition of the Amira software (version 2021.03; Stalling et al., 2005; http://amira.zib.de). Within Amira, the core liners, including about 2 mm of the core rims, were deleted from the data set. Mangan nodules with diameters >~1 mm, open bioturbation traces, an unidentified organism (only present in core SO268-2-200-1 MC18), the natural bioturbated and surficial homogenised sediment were segmented by a marker-based watershed segmentation and visualized in 3D. Subsequently, the sediment components were quantified (MaterialStatistics module; volume per slice) and the mean and standard deviation of the sediment x-ray attenuation (MaterialStatistics module; statistics per slice per label; to avoid marginal averaging effects the sediment label was reduced by three voxels) were determined.